Development of Tomato (Lycopersicum esculentum Mill.) Roots in Every Growth Stage In Flooding Conditions - Rabiatul Jannah; Julianthy Diana Natalia; Odit Ferry Kurniadinata (Indonesian Society for Horticulture (Perhimpunan Hortikultura Indonesia Komisariat Aceh), 2019)
Flooding is a natural phenomenon that often occurs in the rainy season arrives with high rainfall. This phenomenon give an effect to plant growth if it occurs in agricultural areas. This research was carried out at Samarinda, Indonesia. This study uses a completely randomized design non factorial, consists of 4 lavels ie; 4 hours height level 50% flooding (J1), 8 hours height level 50% flooding (J2), 4 hours height level 100% flooding (J3), 8 hours height level 100% flooding (J4), carried out with 4 repetitions. Flooding simulation is carried out 5 times in each growth phases of tomato plants. The data analysis used Anova. If the variance is significantly different, then followed by the LSD (Least Significance Different) at 5%. The results showed that simulation of flooding with times 8 hours height level 50% flooding had a morederate negative effect on tomato plants. The flooding simulation with times 8 hours height level 100% flooding gives the highest negative effect on tomato plants and the root, due to excess water requirements so that plants cannot meet needs of the plants.